2014
DOI: 10.1177/0890334414561061
|View full text |Cite
|
Sign up to set email alerts
|

WIC Peer Counselors’ Perceptions of Breastfeeding in African American Women with Lower Incomes

Abstract: Background African-American women have the lowest breastfeeding rates among all racial/ethnic groups in the United States. Peer counseling is an effective intervention in improving breastfeeding in this population. However, little is known on peer counselors’ perceptions of breastfeeding in African-American women. Objectives As part of a larger qualitative study, the goal of this study was to understand the contextual factors influencing breastfeeding decisions of low-income African-American women from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 41 publications
1
48
0
5
Order By: Relevance
“…In addition, black mothers and/or maternal grandmothers may still positively associate formula with a sign of wealth and status. 35,36 Interventions that seek to support young mothers may wish to focus on this complex relationship, with its benefits and challenges, between the infant's mother and maternal grandmother, 27,37 especially when breastfeeding is not an experience that has been shared by the grandmother in her own parenting history.…”
mentioning
confidence: 99%
“…In addition, black mothers and/or maternal grandmothers may still positively associate formula with a sign of wealth and status. 35,36 Interventions that seek to support young mothers may wish to focus on this complex relationship, with its benefits and challenges, between the infant's mother and maternal grandmother, 27,37 especially when breastfeeding is not an experience that has been shared by the grandmother in her own parenting history.…”
mentioning
confidence: 99%
“…Recent research has revealed that Breastfeeding Peer Counseling Programs have had positive effects on increasing breast-feeding initiation and continuation for black mothers enrolled in WIC (68,69) . Breastfeeding Peer Counseling Programs have discovered that black women tend to place high value on breast pumps as a matter of convenience and a way to exert control over breast-feeding (67) . Moreover, the educational component of the Breastfeeding Peer Counseling Program regarding the benefits of breast milk for infants has resulted in increasing breast-feeding rates among black WIC participants (59,64) .…”
Section: Discussionmentioning
confidence: 99%
“…Not only has research revealed breast-feeding to be less common among WIC participants (58)(59)(60)(61)(62)(63)(64) , it has also revealed that black WIC participants have the lowest breast-feeding rates (59,63) and are significantly less likely to receive breast-feeding advice from their health-care providers and/or WIC counsellors than white participants (59,64,65) . In an effort to improve breast-feeding rates among WIC participants, especially black participants, the WIC programme expanded its breast-feeding education to include the Breastfeeding Peer Counseling Program (66,67) . The WIC peer counsellor must have breast-fed at least one child for 6 months or longer and be a current or previous WIC participant.…”
Section: Discussionmentioning
confidence: 99%
“…Kim (2001), menyebutkan bahwa seorang perempuan bisa mendapatkan informasi mengenai ASI eksklusif dari berbagai sumber, keluarga, teman, media cetak, classes prenatal, dan tenaga kesehatan. Keputusan ibu menyusui (Gross, 2015) untuk memberikan ASI kepada anak mereka dipengaruhi oleh banyak faktor, diantaranya kondisi kontekstual dari ibu tersebut. Diperlukan sebuah pendekatan kesehatan masyarakat untuk promosi ASI yang lebih luas diluar karakterstik individu dari ibu menyusui, seperti riwayat dan sosial budaya yang mendasari pemberian ASI.…”
Section: Hasil Dan Pembahasanunclassified